The Influence of Attitude and Motivation on the Entrepreneurial Interest of Students of the State University of Makassar Economics Education Study Program Class of 2021 - Putrawan, Muh. Rizah; Mustari, Mustari; Nahriana, Nahriana (International Journal of Education, Vocational and Social Science, 2024)
The purpose of this study is to find out how attitudes and motivations affect the entrepreneurial interest of students of the Economic Education program of the State University of Makassar. A total of 100 Economics Education students of the class of 2021 were randomly selected to be respondents using a quantitative methodology. Many linear regressions are used to analyze data. The findings of the analysis show that motivation and attitude have a good and great influence on a person's interest in starting their own business. With X1 representing attitude and X2 representing motivation, the resulting regression equation Y = 13.465 + 0.414X1 + 0.249X2 + ε shows that these two variables have an effect on entrepreneurial interest. Based on the findings of the study, it can be said that motivation and attitude have a positive and significant effect on an individual's interest in starting their own business. Economics Education Student, State University of Makassar. With a coefficient of determination (R2) of 29.3%, attitudes and motivation can explain some of the variations in entrepreneurial desires, while friendships are influenced by unidentified factors.